2021
DOI: 10.1097/ju.0000000000001325
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and Survival Outcomes Associated with Variant Histology Bladder Cancers Managed by Cystectomy with or without Neoadjuvant Chemotherapy

Abstract: Purpose: Although neoadjuvant chemotherapy is associated with a survival advantage in pure urothelial, muscle invasive bladder cancer, the role of neoadjuvant chemotherapy is less clear in variant histology or urothelial carcinoma with divergent differentiation. We compared chemotherapy response and survival outcomes of patients with nonpure urothelial carcinoma histology who were managed with neoadjuvant chemotherapy followed by cystectomy vs cystectomy alone. Materials and Methods:We analyzed 768 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Pathologic complete response was reported in ten studies (4-6,8,10-14,36) while pathologic downstaging was reported in nine studies (4,5,7,8,10,11,(13)(14)(15). S u r v i v a l b e n e f i t w i t h N A C i n V H o f U C w a s demonstrated in two studies (5,14), and specifically with sarcomatoid differentiation (11) and squamous differentiation (6,9).…”
Section: Actual Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pathologic complete response was reported in ten studies (4-6,8,10-14,36) while pathologic downstaging was reported in nine studies (4,5,7,8,10,11,(13)(14)(15). S u r v i v a l b e n e f i t w i t h N A C i n V H o f U C w a s demonstrated in two studies (5,14), and specifically with sarcomatoid differentiation (11) and squamous differentiation (6,9).…”
Section: Actual Resultsmentioning
confidence: 99%
“…There is evidence of improved survival in patients with sarcomatoid differentiation receiving NAC compared to RC alone. (5,14) This may be an alternative therapeutic option in glandular and squamous differentiation, evidence from a single institutional study (12) Findings on the efficacy of neoadjuvant pembrolizumab are preliminary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, BCa treatment had seen little progress. For 30 years, clinicians offered the same, limited range of therapeutics to patients, and the 5-year survival rates were flat (7)(8)(9). Further analysis of the causes of death in patients with BCa showed that tumor-specific deaths account for a large proportion, but the proportion of non-tumor-specific deaths is also surprisingly high, especially heart-specific mortality (10).…”
Section: Introductionmentioning
confidence: 99%